(untitled) (Journal of Sciences & Technology, 2016)
This study reports numerical simulation for 3D laminar forced convection of a nanofluid flow in horizontal annulus with constant heat flux at the outer cylinder will the inner cylinder is considered adiabatic. The numerical model is carried out by solving the governing equation of continuity, momentum and energy using take account for thee finite volume method, with the assistance of SIMPLER algorithm. The results shows that for the Reynolds numbers and Prandtl fixed, the dimensionless velocity profile for the laminar forced convection of a nanofluid consisting of water does not vary with the volume concentration of nanoparticles while the effect of the concentration of nanoparticles on the temperature of the mass is significant nanofluid. These results are consistent with those found in the literature. In general the use of nanofluid with a volume concentration of nanoparticles causes a increase in the coefficient of heat transfer by convection.